Characterization of Sardinella fimbriata and Clarias gariepinus bones - Wan Norasiah Tun Mohd Rosidi; Nurainni Mohd Arshad; Nor Fazliyana Mohtar (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rosidi WNATM, Arshad NM, Mohtar NF. 2021. Characterization of Sardinella fimbriata and Clarias gariepinus bones. Biodiversitas 22: 1621-1626. Calcium is one of the most important minerals required by the human body, which can be directly consumed from milk or any dietary supplement. This study was carried out to determine the calcium content in Fringescale sardinella (Sardinella fimbriata) and catfish (Clarias gariepinus) bones and compare their suitability for human consumption. Fish bones were cleaned, boiled, dried, and ground into powder. Bones from both species were white in color and odorless after drying. The protein content of S. fimbriata was measured to be 20.40 ± 1.61%, while for C. gariepinus it was 19.47 ± 0.61%. Ash content of S. fimbriata and C. gariepinus bones was 62.32 ± 0.08% and 67.9 ± 0.25%, respectively. S. fimbriata bone exhibited 16.4 ± 0.15% moisture, higher than C. gariepinus (7.71 ± 0.14%). The lipid content of S. fimbriata was 0.77 ± 0.17% and for C. gariepinus it was 3.56 ± 0.9%. The solubility of S. fimbriata bone was 23.67 ± 2.65%, higher than that of in C. gariepinus bone (9.02 ± 2.19%). The calcium content found in S. fimbriata and C. gariepinus bones were 4.96 ± 0.13 µg/g and 4.79 ± 0.06 µg/g, respectively. S. fimbriata bone exhibited higher solubility than that of C. gariepinus and was more suitable for human consumption. Overall findings have suggested the calcium from fish bones that may replace commercial calcium in the market, thus meeting the requirements of food safety standards.